Introduction to environmental economics - Hanley, Nick.; Shogren, Jason F.; White, Ben. (Oxford ; New York : Oxford University Press, 2001)
Understanding why environmental problems occur and what best to do about them is much facilitated by an understanding of economics. This book provides an introduction to the subject of environmental economics which does not assume an in-depth prior understanding of economics. Part one explains the fundamental economic concepts, using environmental examples, including markets, environmental evaluation, risk, and trade. Part two then sets these concepts to work in understanding and developing policy responses to some of the major environmental issues of our time. Examples are drawn from all over the world and include such vital global issues as climate change, water pollution, and the loss of biodiversity. An Introduction to Environmental Economics examines both a wide range of environmental case studies and also assesses a variety of economic theories and their approach to environmental issues. Clearly written, global in approach, and theoretically broad-minded, this new text is an ideal introduction both to the study of environmental economics and to the question of how economics can provide tools for improving our global environment.
Part I 1. Economics for the Environment 2. Markets for the Environment 3. Valuing the Environment and Natural Resources 4. Cost-Benefit Analysis and the Environment 5. Environmental Risk 6. Economic Growth and Sustainable Development 7. Strategic Interaction 8. Trade and the Environment Part II 9. Transport and the Environment 10. Rainforests 11. Controlling Water Pollution 12. The Economics of Climate Change 13. Biodiversity 14. Resources and Energy 15. Epilogue
Includes bibliographical references and index.
Keywords: Environmental economics